Peripheral blood progenitor cell (PBPC) counts during steady-state hematopoiesis allow to estimate the yield of mobilized PBPC after filgrastim (R-metHuG-CSF)-supported cytotoxic chemotherapy - Frühauf, Stefan; Haas, Rainer; Conradt, Christian; Martin, Simona; Witt, Barbara; Möhle, Robert; Hunstein, Werner (Blood, 1995)
Peripheral blood progenitor cells (PBPC) can be mobilized using cytotoxic chemotherapy and cytokines. There is a substantial variability in the yield of hematopoietic progenitor cells between patients. We were looking for predictive parameters indicating a patient's response to a given mobilization regimen. Multiparameter flow-cytometry analysis and clonogenic assays were used to examine the hematopoietic progenitor cells in bone marrow (BM) and peripheral blood (PB) before filgrastim (R-metHuG-CSF; Amgen, Thousand Oaks, CA)-supported chemotherapy and in PB and leukapheresis products (LPs) in the recovery phase. Fifteen patients (four with high-grade non-Hodgkin's lymphoma [NHL], two with low-grade NHL, two with Hodgkin's disease, two with multiple myeloma, three with breast cancer, one with ovarian cancer, and one with germ cell tumor) were included in this study. The comparison of immunofluorescence plots showed a homogenous population of strongly CD34+ cells in steady-state and mobilized PB whereas in steady-state BM, the CD34+ cells ranged from strongly positive with continuous transition to the CD34- population. Consistent with the similarity in CD34 antigen expression, a correlation analysis showed steady-state PB CD34+ cells (r = .81, P < .001) and colony-forming cells (CFCs; r = .69, P < .01) to be a measure of a patient's mobilizable CD34+ cell pool. Individual estimates of progenitor cell yields could be calculated. With a probability of 95%, eg, 0.4 steady-state PB CD34+ cells × 106/L allowed to collect in six LPs 2.5 × 106 CD34+ cells/kg, the reported threshold-dose of progenitor cells required for rapid and sustained engraftment after high-dose therapy. For the total steady-state BM CD34+ cell population, a weak correlation (r = .57, P < .05) with the mobilized CD34+ cells only became apparent when an outlier was removed from the analysis. Neither the CD34+ immunologic subgroups defined by the coexpression of the myeloid lineage-associated antigens CD33 or CD45-RA or the phenotyp-ically primitive CD34+/HLA-DR- subset nor the BM CFC count had a predictive value for the mobilization outcome. This may be caused by the additional presence of maturing progenitor cells in BM, which express lower levels of the CD34 antigen and do not circulate. Our results permit us to recognize patients who are at risk to collect low numbers of progenitor cells and those who are likely to achieve sufficient or high progenitor cell yields even before mobilization chemotherapy is administered.